Hubungan Intensitas Menonton Televisi dan Pola Asuh Orang Tua dengan Prestasi Belajar pada Siswa SDN 01 Baruga Kota Kendari Tahun 2016 - Lampasa, Eka Pratiwi; Rudi, Islaeli (Jurnal Gizi Ilmiah, 2017)
From the results of the initial survey of researchers at SDN 01 Baruga, Kendari City, the average value of report cards obtained by several students, especially grades IV, V and VI in the first semester of the 2015 academic year/ 2016 there were 67 students who had an average score of <70 and 56 students who had an average score of 70. The aim of this research is to find out the relationship between the intensity of watching television and parenting style with the learning achievement of the students of SDN 01 Baruga, Kendari City. This type of research uses observational analysis with a cross sectional approach. The number of samples was 81 respondents using the proportional random sampling technique. There are two variables in this study, namely the intensity of watching and parenting as an independent variable and learning achievement as the dependent variable. Data analysis using chis square test. The results in this study indicate that there is a relationship between the intensity of watching and learning achievement in students with a score of X2 count 15.668 > X2 table 3.841 and the value of C = 0.000 > 0.05. There is a relationship between parenting style and learning achievement in students of SDN 01 Baruga Kendari City with a value of X2 count 10.279 > X2 table 3.841 and a value of C = 0.003 <0.05. Thus, it can be concluded that the intensity of watching television and parenting patterns are related to learning achievement in students at SDN 01 Baruga, Kendari City. It is suggested that the school cooperates with the parents of students to pay attention to the improvement of student achievement.